Réponses

  • Utilisateur Brainly
2014-06-09T19:32:16+02:00
64 :

A = -a-b-a+b-a-b-a+b
   = -4a

B = -x+5-x-2+x+4+x-1
   = 6

C = 3-a-b-3-a-b+3-a-b
   = 3-3a-3b
   = -3a-3b+3
  =  3(-a-b+1)
65 : A = 3x+6-x+1 = 2x+7
B = 12x+4-4x-7 = 8x-3
C = 7x-21+3x-6+2x-2 = 12x-29
erreur C
2014-06-09T20:08:43+02:00
Bonsoir
a) -a-b+a+b-a-b-a+b = -2a

b) -x-5 -x-2+x+4+x+1 = -2

c) 3 -a-b-a-b-3+3-a-b = -3a -3b +3

a) 3x +6 -x +1 = 2x +7

b) 12x +4 -4x -7 = 8x -3

c) 7x -21 + 3x +6 +2x - 2 = 12x - 17
b) -x-5 -x-2+x+4+x+1 = -2 erreur pour le dernier 1 pk +1? +(x-1) = x-1 pas x+1